Diagnostic Value of the Triple Combination of Serum Heparin-Binding Protein, Procalcitonin, and C-Reactive Protein in Children with Acute Bacterial Upper Respiratory Tract Infection. (10th March 2022) - Yang, Xiuqin; Zhang, Yumei; Lin, Hai; Zhong, Hui; Wu, Zhihui
Abstract : To investigate the role of the triple combination serum heparin-binding protein (HBP), procalcitonin (PCT), and C-reactive protein (CRP) in children with acute bacterial upper respiratory tract infection (ABURTI). A total of 130 children with upper respiratory tract infection admitted to the Department of Pediatrics of Fujian Maternity and Child Health Hospital from September 2019 to January 2021 were selected as the research group. According to the results of pathogenic analysis, children were further subdivided into a bacterial infection group ( n  = 67) and a viral infection group ( n  = 63). Additionally, 65 children who underwent physical examinations in our hospital during the same period were collected and included into the control group ( n  = 65). All patients selected were treated with cefixime granules orally for 5 days. Serum HBP level, serum PCT level, and serum CRP level were measured by double antibody Sandwich Enzyme Linked Immunosorbent Assay (ELISA), fluorescence method, and immunoturbidimetric assay, respectively. The expression levels of the three indicators in the serum of all subjects were compared, and the receiver operating characteristic (ROC) curve was used to analyze their diagnostic value in children with ABURTI. Furthermore, according to clinical efficacy of children with bacterial infections, they were divided into a good efficacy group (markedly effective) and a poor efficacy group (effective + ineffective) to compare serum HBP, PCT, and CRP levels between the two groups. The ROC curve was drawn to analyze the value of the three indicators in predicting the curative effect in children with ABURTI. Pearson test was used to analyze the correlation among the expression of HBP, PCT, and CRP. Results showed that the expression levels of HBP, PCT, and CRP in the serum of children in the bacterial infection group were significantly higher than those in the other two groups. The positive rates of HBP, PCT, and CRP in children in the bacterial infection group were also significantly higher than those of the other two groups. The area under the curve (AUC) of the combined diagnosis of HBP, PCT, and CRP was 0.973, which was significantly higher than that of the single detection by any of the three indicators, which were 0.849, 0.819, and 0.854, respectively. The expression levels of HBP, PCT, and CRP in the serum of children in the good efficacy group were significantly lower than those in the poor efficacy group, and the AUC of the triple combination for predicting treatment efficacy was 0.959. Pearson test showed that there was a positive correlation between the serum expression of HBP, PCT, and CRP in children. HBP, PCT, and CRP were highly correlated in children with ABURTI, and their combined detection was of high diagnostic value among ABURTI patients, indicating that the three were expected to become potential indicators for efficacy prediction.